PERBEDAAN PENGGUNAAN MEDIA VIDEO ANIMASI DAN KARTU BERGAMBAR TERHADAP PENCEGAHAN SEXUAL ABUSE PADA ANAK USIA SEKOLAH DI SD NEGERI 5 MEGANG SAKTI - Sri Tirtayanti; Fahmi Ristayani (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2021)
The problem of sexual education is getting less attention from parents. Most parents think thatsexual education is the responsibility of the school. Sex education that can be done to children isby using audiovisual media and picture cards. The purpose of this study was to determine thedifferences in the use of animated video media and picture cards on the prevention of sexualabuse in school-age children. This type of research is a quasi-experimental design with Two GroupDesign. The sample is students of SDN 5 Megang Sakti, totaling 30 students. The samplingtechnique used was purposive sampling. This study uses univariate and bivariate data analysiswith dependent t test and independent sample t test. The results showed that the use of animatedvideo media and picture cards had an effect on increasing knowledge of sexual abuse preventionin school-age children with value <0.05. Based on statistical tests, there are significant differencesin the use of video media and picture cards with a value of value = 0.036. Both media are effectivein increasing knowledge, but there is a difference of 2.3 between animated video media andpicture cards which means that the use of animated video media is more effective than picturecards.